Effectiveness of Chemical Scarification Methods on the Early Germination of Different Varieties of Date Palm in Kashere, Gombe State, Nigeria - Usman, Magaji G.; I. Musa; M. U. Galadima; M.A. Muhamman; A. Salem; M.S. Isyaku; I. Muhammad; Z. A. Abubakar; A. Dattijo; M.S. Saidu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Date palm is one of the most important trees in semi-arid and dry areas of the world. Dates are rich in carbohydrates, vitamins and minerals, they have immense importance as a healthy food as well as a desert fruit. The fruit contains fructose and glucose as the major sugar components which make it an important source of sugar to persons who cannot tolerate sucrose. The tree provides food, fuel, shelter and is used in manufacturing of different handicrafts. The primary cause of datepalm seed (Phoenix dactylifera L.) dormancy is its hard seed coat structure, which makes it difficult for the seed to absorb water during germination. This study aimed to examine the effect of chemical scarification treatments which could effectively enhance and reduce datepalm (Phoenix dactylifera L.) number of days to seed germination in Kashere, Gombe State. The experiment consisted of ten different varieties of datepalm sourced from Nigerian Institute for Oil Palm Research, Jigawa State and two chemical treatments (H2SO4 and NaOH) together with a control (water) laid out in a Randomized Complete Block Design in two replications. It was significantly observed that the varieties differ in their rate of germination with Shiwarin (25.83 days) germinating earlier than the other varieties studied. Similarly, chemical treatment was found effective in promoting germination rate and germination percentage of the studied datepalm varieties. Furthermore, the varieties were categorized based on the number of days to germination and germination percentage with Galamawa and Shiwarin varieties showing potential for early germination and high germination percentage. According to the findings reported here, date palm seed exhibited exogenous dormancy that is entirely enforced by the hard seed coat. Chemical scarification is a viable method that can enhance early germination of date palm seeds.